Response of Late Sowing on the Yield and Yield Contributing Character of Different Varieties of Mustard and Rapeseed in Coastal Area of Barguna (Bangladesh Journal of Scientific and Industrial Research, 2008)
An experiment was carried at Multi Location Testing site Barguna to determine suitable variety of mustard (Brassica species) for the late sowing condition for the coastal area of Bangladesh during rabi season of 1998-1999 and 1999-2000. Four varieties of mustard such as Daulat, Rai-5, Improved tory-7, and Ishurdi local with four sowing dates viz.15 Nov, 23 Nov, 30 Nov. and 7 Dec. were used for the experiment. The experiment was laid out in a split plot design with sowing date in the main plot and varieties in the sub plot. The results revealed that the variety Daulat (1035 kg/ha) and Ishurdi local (1014 kg/ha) produced identically superior yield irrespective of sowing time. 15 November (1164 kg/ha) and 23 November (1002 kg/ha) recorded identically superior yield irrespect of variety. Daulat and Ishurdi local variety sowing could be delayed up to 30 November to obtain a profitable yield of (872 kg/ha) and (940 kg/ha) respectively which was still economically profitable. Key words: Mustard and rapes, Late sowing , variety, Yield, coastal area. Bangladesh J. Sci. Ind. Res. 42(4), 441-448., 2007